Regulation of the microprocessor by post-translational modifications - Leong, Ka Weng; Chong, Mark M. W. (Frontiers in Cell and Developmental Biology, 2025)
The Microprocessor is an essential protein complex that is responsible for the first processing step in the biogenesis of canonical microRNAs. The core of this complex is composed of two proteins, the ribonuclease III enzyme DROSHA and its double-stranded RNA-binding cofactor DGCR8. Dysregulation of the expression of the Microprocessor contributes to many disorders, including pluripotency defects, immune dysfunction, cancers, and neurological diseases. Multiple post-translational modifications (PTMs) have been reported for DROSHA and DGCR8, and these are thought to play roles in regulating Microprocessor levels and its functions; however, most of these PTMs remain functionally uncharacterized. In this review, we discuss these PTMs of the Microprocessor, focusing on phosphorylation, acetylation, ubiquitination, and SUMOylation, and how these modifications are thought to regulate protein stability, microRNA production, and other non-canonical Microprocessor activities.